George Santayana’s Sense Of Beauty And Its Reflection In Contemporary Plastic Art - Mohsin Shaabeth, Adel Munem Abdul; Mohsin Shaabeth, Suhad Munem Abdul; Abbas Khafaji, Turath Ameen (Opción, 2019)
Plastics, herewith expected as materials dependent on natural polymers which can be controlled to frame films, strands, froths or three-dimensional articles, turned into a modern and family pertinent material amid the years between the world wars yet it is just since after the Second World War with the pres- entation of new classes of engineered polymers, and later during the 1960s as an outcome of monetary improvement, that polymeric materials have turned out to be inescapable in our day by day life. In the meantime, engineered and artificially altered characteristic polymer ancient rarities began to show up in accumulations and exhibitions, particularly since the improvement of present day historical centers (Carrier, 2018). Items in part or totally made of plastics might be found in practically all global accumulations gave to science and innovation, current history, plan and plastic arts, and their extent is probably going to increment with time